2004
DOI: 10.1080/0960310042000233458
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Indian commercial banks during the reform period

Abstract: This article contributes to the banking efficiency literature by measuring technical efficiency of banks in four different ownership groups in India during the reform period, 1992-1999. It employs the stochastic frontier function methodology for panel data. The results indicate that the efficiency of raising interest margin is time invariant while the efficiencies of raising other outputs-non-interest income, investments and credits are time varying. The state bank group and foreign banks are more efficient th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 10 publications
2
67
0
Order By: Relevance
“…The results indicate that total factor productivity growth has not been significant post deregulation and importantly, there was no evidence of narrowing of performance differentials across ownership category following deregulation. Subsequently, Shanmugam and Das (2004) observed that technical efficiency of raising interest margin of Indian commercial banks during 1992-99 is time invariant, while the efficiencies of raising other outputs-non-interest income, investments and credits are time varying. Based on nonparametric approach, Rammohan and Ray (2004) and Das et al (2005) compared the various efficiency measures of banks across different ownership groups during the post liberalization period.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that total factor productivity growth has not been significant post deregulation and importantly, there was no evidence of narrowing of performance differentials across ownership category following deregulation. Subsequently, Shanmugam and Das (2004) observed that technical efficiency of raising interest margin of Indian commercial banks during 1992-99 is time invariant, while the efficiencies of raising other outputs-non-interest income, investments and credits are time varying. Based on nonparametric approach, Rammohan and Ray (2004) and Das et al (2005) compared the various efficiency measures of banks across different ownership groups during the post liberalization period.…”
Section: Review Of Literaturementioning
confidence: 99%
“…State-owned banks cover nationalised banks (majority equity holding being with the Government), the State Bank of India (majority equity holding being with the Reserve Bank of India) and its associate banks (majority of interest to examine if the diversification of the ownership of state-owned banks and the penetration of private and foreign banks has had an impact on profit efficiency. Third, studies on efficiency in Indian banks have typically examined the cost and technical efficiency (Bhattacharya et al, 1997;Das, 1997;Shanmugam and Das, 2004;Das et al, 2005;Das and Ghosh, 2006;Chatterjee, 2006). 2 Banking sector liberalization, in its wake, has lead to significant improvements in the quality of output (ATM, internet banking, convenient banking hours, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…To measure the extent to which banks aggravate or reduce inflation, it is assumed that they use capital, labour and other nonfinancial inputs to provide services, deposits and advances for account holders (Shanmugam and Das 2004). The following function constructs a cost index (C i ) that includes all of these expenses.…”
Section: Methodsmentioning
confidence: 99%
“…Economies experiencing high interest rates subsequent to high inflation were empirically found to generate frail banking sectors (Haslag and Koo 1999;Bittencourt 2006). Time series analysis and case studies on emerging economies, such as India (Shanmugam and Das 2004), Brazil (Bittencourt 2007) and Pakistan show the damaging effects of inflation on financial development.…”
Section: The Empirical Modelmentioning
confidence: 97%
“…3 More recently, Shanmugam and Das (2004) used a larger data set to estimate efficiency of Indian banks using various stochastic frontiers. But they too did not study profit performance of banks.…”
Section: Introductionmentioning
confidence: 99%